2011
DOI: 10.6007/ijarbss.v1i2.16
|View full text |Cite
|
Sign up to set email alerts
|

Computer Usage As Instructional Resources For VocationalTraining In Nigeria

Abstract: The use of computers has become one of the driving forces in the delivery of instruction of today's vocational education and training (VET) in Nigeria. Though computers have become increasingly accessible resources for educators to use in their teaching activities, most teachers are still unable to integrate it in their teaching and learning processes. Computers are used to improve teaching quality where quality is very expensive to reproduce, or to substitute for the lack of teachers, or schooling opportuniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…If Nigeria is serious about its Human Development Index, it must prioritise adult education among its adult population to benefit from these global advancements. It must also embrace the adoption of the Internet in its application to adult education [1]. However, a challenge arises due to the prevalent network issues and other factors impeding effective internet-based learning in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…If Nigeria is serious about its Human Development Index, it must prioritise adult education among its adult population to benefit from these global advancements. It must also embrace the adoption of the Internet in its application to adult education [1]. However, a challenge arises due to the prevalent network issues and other factors impeding effective internet-based learning in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Computer usage is becoming an increasingly accessible resource for educators to use in their teaching activities, and a driving force in the delivery of instruction of today's TEE in some countries. However, in developing countries like Nigeria many teachers are still unable to integrate it into their teaching and learning processes [20]. Computer assisted instruction (CAI) has been identified as one of the methods of integrating Information and Communication Technology (ICT) into classrooms [16].…”
Section: Introductionmentioning
confidence: 99%
“…Computer devices have become the driving force in the delivery of instruction of today's education in Nigeria (Oguzor, 2011).Research shows that using computer devices and other digital innovations, including computer games, androids, podcasts, blogs, wikis, e-learningapplications, and other classroom technologies in teaching and learning, is vital in influencing and shaping learner's performance and promotes schoolwork engagement(Al-Jaberi, 2018; 2020)investigated the effects of digital learning materials (DLMs) on nursing students' mathematics learning. The study adopted a pre-test/post-test control group design, and the result found that the mathematics learning of students undergoing DLMs training improved significantly.Chen (2017) explored the effect of digital game-based instruction on students' learning motivation and achievement using 326 students from Taiwan universities as the research participants.…”
mentioning
confidence: 99%